2019
DOI: 10.1055/s-0039-1685452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Thrombin Generation Methods, CAT and ST-Genesia, in Liver Transplant Patients

Abstract: Background During liver transplantation (LT), thrombin generation (TG) is altered. The most frequently used assay for TG is the Calibrated Automated Thrombogram (CAT). It is designed for series of plasmas and is semi-automated. Complete automation has led to a new device, the ST-Genesia, enabling quantitative standardized TG evaluation. Objective The aim of this observational study was to compare the TG results of the CAT and the ST-Genesia on frozen-thawed plasma samples prepared from the blood of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…We detected opposite results using the DrugScreen, which showed higher peak and ETP values, perhaps because it has a high TF concentration and low factor VII levels, which are common in liver disease. The lag time was shortest using the ThromboScreen reagent, while BleedScreen and CAT exhibited similar results 9 . In the present study, DrugScreen exhibited a shorter lag time than CAT, as well as higher ETP and peak values.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We detected opposite results using the DrugScreen, which showed higher peak and ETP values, perhaps because it has a high TF concentration and low factor VII levels, which are common in liver disease. The lag time was shortest using the ThromboScreen reagent, while BleedScreen and CAT exhibited similar results 9 . In the present study, DrugScreen exhibited a shorter lag time than CAT, as well as higher ETP and peak values.…”
Section: Discussionsupporting
confidence: 67%
“…Few studies have compared CAT with ST Genesia 9 . Recently, the plasma levels of direct oral anticoagulants (DOACs) were shown to correlate with the lag time and peak height of the DrugScreen test 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only one study compared TG measurements of CAT and ST‐Genesia. The results of ST‐Genesia differed from results obtained with the CAT in a cohort of patients with liver transplants 26 . Thus, ST‐Genesia and CAT cannot be compared directly in terms of absolute measurements.…”
Section: Discussionmentioning
confidence: 82%
“…Two recent publications compared CAT with STG‐BleedScreen (BLS) and STG‐ThromboScreen (TS). TG parameters obtained with CAT using blood samples from patients undergoing liver transplant showed different results compared to those with ST Genesia BLS and TS 22 . In contrast, in another study on healthy volunteers, BLS showed a positive correlation with peak thrombin and ETP in CAT using 1 pM tissue factor, while TS correlated only with peak thrombin in CAT with 5 pM TF in the absence of thrombomodulin and with ETP in the presence of thrombomodulin 23 .…”
Section: Discussionmentioning
confidence: 99%